Existentialism by Soren Aabye Kierke gaard: Indiana in Indiana Jones and the Last Crusade as a Representation of an “Authentic” Human Being - Asmiliasari, Chintia (Paradigma: Jurnal Kajian Budaya, 2011)
Existentialism of Soren Aabye Kierkegaard is a study focusing on the individual existence as an authentic creature. Existentialism can only be achieved by an individual’s boldness and belief to commit responsibly to a decision he has made. The decision made by each individual should be based on his subjective truth and should not be influenced by the collective truth called the objective truth. The subjective truth will later lead each individual to his way finding an absolute truth, although despair and uncertainty haunt every decision he has made. A totality of believing in making decision and holding the commitment into it will finally bring an individual to the existence of himself as the most authentic creature. Indiana in Indiana Jones and the Last Crusade represents an individual with a quality of Soren Aabye Kierkegaard’s Existentialism concept. It is begun from Indiana’s imprisonment in his objective truth as an archeologist, his despair at making a choice and decision, in which finally turned him into someone who finds an absolute truth based on his subjective truth. At last, his finding has led him into an existence and authentic individual.